Distinct roles for interleukin-23 receptor signaling in regulatory T cells in sporadic and inflammation-associated carcinogenesis - Jacobse, Justin; Pilat, Jennifer M.; Li, Jing; Brown, Rachel E.; Kwag, Aaron; Buendia, Matthew A.; Choksi, Yash A.; Washington, M. Kay; Williams, Christopher S.; Markham, Nicholas O.; Short, Sarah P.; Goettel, Jeremy A. (Frontiers in Oncology, 2024)
Introduction: The pro-inflammatory cytokine interleukin-23 (IL-23) has been implicated in colorectal cancer (CRC). Yet, the cell-specific contributions of IL-23 receptor (IL-23R) signaling in CRC remain unknown. One of the cell types that highly expresses IL-23R are colonic regulatory T cells (Treg cells). The aim of this study was to define the contribution of Treg cell-specific IL-23R signaling in sporadic and inflammation-associated CRC. Methods: In mice, the role of IL-23R in Treg cells in colitis-associated cancer (CAC) was investigated using azoxymethane/dextran sodium sulphate in wild-type Treg cell reporter mice (WT, Foxp3YFP-iCre), and mice harboring a Treg cell-specific deletion of IL-23 (Il23rΔTreg). The role of IL-23R signaling in Treg cells in sporadic CRC was examined utilizing orthotopic injection of the syngeneic colon cancer cell line MC-38 submucosally into the colon/rectum of mice. The function of macrophages was studied using clodronate. Finally, single-cell RNA-seq of a previously published dataset in human sporadic cancer was reanalyzed to corroborate these findings. Results: In CAC, Il23rΔTreg mice had increased tumor size and increased dysplasia compared to WT mice that was associated with decreased tumor-infiltrating macrophages. In the sporadic cancer model, Il23rΔTreg mice had increased survival and decreased tumor size compared to WT mice. Additionally, MC-38 tumors of Il23rΔTreg mice exhibited a higher frequency of pro-inflammatory macrophages and IL-17 producing CD4+ T cells. The decreased tumor size in Il23rΔTreg mice was macrophage-dependent. These data suggest that loss of IL-23R signaling in Treg cells permits IL-17 production by CD4+ T cells that in turn promotes pro-inflammatory macrophages to clear tumors. Finally, single-cell RNA-seq analysis of a previously published dataset in human sporadic cancer, revealed that IL23R was highly expressed in CRC compared to other cancers and specifically in tumor-associated Treg cells. Conclusion: Inflammation in colorectal carcinogenesis differs with respect to the contribution of IL-23R signaling in regulatory T cells.